Answer:
The statement 'If the reactions of A⟶D are rearranged, they become non spontaneous.' is false
Step-by-step explanation:
Step 1: Data given
Reaction 1 (A⟶B) has a ΔG=+3 kJ/mol
Reaction 2 (B⟶C) has a ΔG=−6kJ/mol
Reaction 3 (C⟶D) has a ΔG=+1 kJ/ mol.
Step 2:
To be spontaneous ΔG should be negative (ΔG<0)
For reaction A⟶D; ΔG = 3kJ/mol -6kJ/mol + 1 kJ/mol = -2 kJ/mol
This means for the reaction A⟶D; the reaction is spontaneous
This means for the reaction D⟶A; ΔG = 2kJ/mol, so the reaction is non-spontaneous
For reaction 1 and 3 the reaction is ,non-spontaneous (but the reverse reaction is). Reaction 2 is driving reactions 1 and 3 forward. A⟶D is thermodynamically spontaneous.
The statement 'If the reactions of A⟶D are rearranged, they become non spontaneous.' is false